Fixed effects estimation of the intensive and extensive margins of irrigation water demand - Hendricks, Nathan P.; Peterson, Jeffrey M. (My University, 2012)
Irrigation water demand is estimated using field-level panel data from Kansas over 16 years. The cost of pumping varies over time due to changes in energy prices and across space due to differences in the depth to water. Exploiting this variation allows us to estimate the demand elasticity while controlling for field-farmer and year fixed effects. Fixed effects also allow us to control for land use without an instrument or assumptions about the distribution of errors. Our estimates of water demand are used to calculate the cost of reducing irrigation water use through water pricing, irrigation cessation, and intensity-reduction programs.
Keywords: Fixed effects; High Plains Aquifer; Water demand